Week 6 Assignment

Week 6 Assignment - Week 6 Assignment Section 4.1 1. 27 = 9...

Info iconThis preview shows pages 1–5. Sign up to view the full content.

View Full Document Right Arrow Icon

Info iconThis preview has intentionally blurred sections. Sign up to view the full version.

View Full DocumentRight Arrow Icon

Info iconThis preview has intentionally blurred sections. Sign up to view the full version.

View Full DocumentRight Arrow Icon
This is the end of the preview. Sign up to access the rest of the document.

Unformatted text preview: Week 6 Assignment Section 4.1 1. 27 = 9 * 3 = 3 36 9 * 4 4 6. 45 = 3 * 15 = -3-75 -5 * 15 5 9. 12xy = 6y * 2x = 2x 42y = 6y * 7 7 13.-14y 3 = 14y 2 * -y = -y 56xy 2 14y 2 * 4x 4x 16. 60x 3 z = 4x 2 * 15xz = 15x 2-64xyz 2 4xz 2 * 16y 16yz 19. x 2- 4 = (x + 2)(x - 2) = x - 2 x 2 + 2x x(x + 2) x 21. 18x + 12 = 6(3x + 2) = 3x + 2 12x - 6 6(2x - 1) 2x - 1 23. a 2 + 7a + 10 = (a + 5)(a + 2) = a + 5 a 2- 7a - 18 (a - 9)(a + 2) a - 9 26. 4n 2- 15n - 4 = (4n + 1)(x + 1) = 4n + 1 7n 2- 30n + 8 (7n - 8)(4n - 2) 7n - 2 30. 4x 2 + 8x = 4x(x + 2) = 4x x 3 + 8 (x + 2)(x 2- 2x + 4) x 2- 2x + 4 37. 5y 2 + 22y + 8 = (5y + 2)(y + 4) = y + 4 25y 2- 4 (5y + 2)(5y - 2) 5y - 2 41. 4x 2 y + 8xy 2- 12y 3 = 4y(x 2 + 2xy - 3y 2 ) = 4y(x + 3)(x - y) = 2(x + 3y) 18x 3 y - 12x 2 y 2- 6xy 3 6xy(3x 2- 2xy - y 2 6xy(3x + y)(x - y) 3x(3x + y) 44. x 4- 2x 2- 15 = (x 2 + 3)(x 2- 5) = x 2- 5 2x 4 + 9x 2 + 9 (x - 5)(2x + 3) 2x 2 + 3 48. 64x 4 + 27x = x(64x 3 + 27) = 64x 3 + 27 = (4x + 3)(16x 2- 12x + 9) 12x 3- 27x 2- 27x 3x(4x 2- 9x - 9x) 3(4x + 3)(x - 3) 3(4x + 3)(x - 3) 16x 2- 12x + 9 __________________ (4x + 3) 64x 3 + 0x 2 + 0x + 27 (-)64x 3 + 48x 2 __________________-48x 2 (-)-48x 2- 36x __________________ 36x + 27 (-) 36x + 27 __________________ 0 = ( 4x + 3 )(16x 2- 12x + 9) = 16x 2- 12x + 9 3(4x + 3)(x - 3) 3(x - 3) 50. -6x 3- 21x 2 + 12x = -3x(2x 2 + 7x - 4) = -3x(2x - 1)(x - 1)-18x 3- 42x 2 + 120x -6x(3x 2 + 7x - 20) 2(3x - 5)(x - 1) 51. xy + ay + bx + ab = y(x + a) + b(x + a) = (x + a)(y + b) = y + b xy + ay + cx + ac y(x + a) + c(x + a) (x + a)(y + c) y + c 55. 5x 2 + 5x + 3x + 3 = 5x(x + 1) + 3(x + 1) = (x + 1)(5x + 3) = x + 1 5x 2 + 3x - 30x - 18 x(5x + 3) - 6(5x + 3) (5x + 3)(x - 6) x - 6 58. nr - 6 - 3n + 2r = nr - 3n + 2r - 6 = n(r - 3) + 2(r - 6) = (r - 3) + (r - 6) = r - 3 nr + 10 + 2r + 5n nr + 5n + 2r + 10 n(r + 5) + 2(r + 10) (r + 5) + (r + 10) r - 5 59. 5x - 7 = -1(-5x + 7) = -1(7 - 5x) = -1 7 - 5x (7 - 5x) (7 - 5x) 61. n 2- 49 = (n + 7)(n - 7) = (n + 7)(n - 7) = n + 7 = -n - 7 7 - n -1(-7 + n) -1(n - 7) -1 63. 2y - 2xy = 2y(1 - x) = 2y(1 - x) = -2y(x - 1) = -2y = -2 x 2 y - y y(x 2- 1) y(x + 1)(x - 1) y(x + 1)(x - 1) y(x + 1) x + 1 68. x 2 + 2x - 24 = (x + 4)(x - 6) = (x + 4)(x - 6) = (x + 4)(x - 6) = (-x - 6) = -x - 6 20 - x - x 2 (4 + x)(5 - x) -1(-4 + x)(5 - x) -1(x + 4)(x - 5) x - 5 x - 5 Section 4.2 3. -4 * 18 = -4 * 9 * 2 = -4 9 30 9 15 * 2 15 5. 3 * -6 = 3 * - 6 = 3-8 12 -8 2 * 6 16 7. (-5 ) 6 = - 5 * 7 = 5 7 7 7 6 6-1 2 9. -9 27 = -9 * 10 = -9 * 10 = -2 5 10 5 27 5 27 3 1 3 11. 4 * 6 4 = 4 * 6 * 15 = 4 * 2 * 3 * 3 * 5 = 10 9 11 15 9 11 4 3 * 3 11 4 11 1 13. 6xy * 30x 3 y = 6(30)x 4 y 2 = 6 * 30x 4 y 2 = 2 * 5x 3 = 5x 3 9y 4-48x 9(-48)xy 4 9 -48xy 4 3 -8y 2-12y 2 4 15. 5a 2 b 2 * 22a 3 = 5(22)a 5 b 2 = 22 * 5a 3 = 2 * a 3 = 2a 3 11ab 15ab 2 11(15)a 2 b 3 11 15b 1 3b 3b 16. 10a 2 * 15b 3 = 10(15)a 2 b 3 = 10 * 15a 2 b 3 = 5 * 3b = 15b 5b 2 2a 4 5(2)a 4 b 2 5 2a 4 b 2 1 1a 2 a 2 3 17. 5xy * 18x 3 y 2 = 5(18)x 3 y 2 = 5 * 18x 3 = 1 * 9 x 3 =...
View Full Document

Page1 / 49

Week 6 Assignment - Week 6 Assignment Section 4.1 1. 27 = 9...

This preview shows document pages 1 - 5. Sign up to view the full document.

View Full Document Right Arrow Icon
Ask a homework question - tutors are online